2009
DOI: 10.1002/ptr.2726
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Glycyrrhiza glabra extracts and its active constituent glabridin

Abstract: Glabridin, an active constituent of Glycyrrhiza glabra roots, was found to be active against both yeast and filamentous fungi. Glabridin also showed resistance modifying activity against drug resistant mutants of Candida albicans at a minimum inhibitory concentration of 31.25-250 microg/mL. Although the compound was reported earlier to be active against Candida albicans, but this is the first report of its activity against drug resistant mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…Fatima et al, (2009) For the Candida strains in which considerable antifungal effect were observed, the effect on biofilm formation was carried out, namely to C. glabrata strains (ATCC2001, D1 and 513100) and C. tropicalis (ATCC750 and T2.2). Despite C. tropicalis strains, namely AG1 and T2.2, as well as ATCC750, 12 and 519468 have evidenced a similar response to the extract, a representative strain of each group was selected.…”
Section: Resultsmentioning
confidence: 99%
“…Fatima et al, (2009) For the Candida strains in which considerable antifungal effect were observed, the effect on biofilm formation was carried out, namely to C. glabrata strains (ATCC2001, D1 and 513100) and C. tropicalis (ATCC750 and T2.2). Despite C. tropicalis strains, namely AG1 and T2.2, as well as ATCC750, 12 and 519468 have evidenced a similar response to the extract, a representative strain of each group was selected.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal effects of G. glabra extract, and its active constituent glabridin, on antibiotic-resistant Candida albicans species were studied in different studies (9). The current research showed antifungal effects of G. glabra extracts on C. albicans species.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, Glycyrrhiza glabra might be useful in the treatment of diarrhea caused by rotavirus infection [16]. Antifungal activity of liquorice extract is due to its active compound identified as glabridin (3-(2',4'-dihydroxyphenyl)-8-dimethylpyrano [8,7-e]chroman) which also demonstrates the resistance modifying activity against drug resistant mutants Candida albicans and Aspergellus niger [17]. The in-vitro and in-vivo anti-malarial activity of 18-β-glycirrhetic acid an active constituent of Glycyrrhiza glabra was also found to be effective [18].…”
Section: Therapeutic Potentials and Traditional Usesmentioning
confidence: 99%